Stabilization interventions in the treatment of traumatized refugees: A scoping review - Irja Rzepka-Marot; Nadja Gebhardt; Jonathan Nowak; Bastian Bruns; Hans-Christoph Friederich; Christoph Nikendei (Cambridge Prisms: Global Mental Health)
Refugees and forced migrants are particularly susceptible to trauma-related disorders, due exposure to traumatic events before, during or after displacement. In trauma therapy, the concept of psychological stabilization refers to the improvement of a patient’s capacity to manage symptoms and emotions associated with traumatic experiences. While exposure-based therapies are widely recommended for treating posttraumatic stress disorder (PTSD), stabilizing interventions may offer a valuable alternative, particularly given the unique challenges in refugee care. This scoping review aims to provide a comprehensive overview of stabilizing, non exposure-based interventions for traumatized refugees A systematic search identified 31 relevant studies featuring diverse interventions, settings, and outcomes. Most studies showed a significant reduction in PTSD symptoms compared to waitlist (six studies), treatment as usual (three studies) and pre-post analyses (nine studies), though nine studies found no difference between intervention and comparison group. Notably, two studies found the stabilizing approach less effective than the comparison group, and two reported no symptom reduction in pre-post analysis. Heterogenity among the examined interventions as well as living conditions was high and limited the generizability of the results. Further studies should take these environmental factors into consideration.